ANCAMAN DAN PELUANG AI (ARTIFICIAL INTELLIGENCE) DALAM DUNIA PENDIDIKAN - Vioni Saputri; Prawira, Ilham Abdi; Nasyariah Siregar (Global Action and Education for Society, 2025)
Practical technological developments that have occurred in the last few decades have given rise to a technological innovation that is currently booming, namely the presence of Artificial Intelligence (AI). The performance and intelligence are made to almost resemble humans. The interactions carried out can take place without involving humans, due to the help of AI itself. AI intelligence in Indonesia has been widely used in various sectors, namely the education sector. This research aims to determine the threats and opportunities of AI in the world of education. Using phenomenological qualitative research methods. The results of this research are 1) The threat presented by AI itself creates dependency, thereby reducing thinking power, increasing levels of plagiarism, and the risk of errors in obtaining knowledge. 2) Opportunities presented by utilizing learning resources, fulfilling assignments help in terms of flexibility, and providing feedback. 3) The role of academics is to accompany students in the stages of writing and assignments, if they need to be given guidance to know that each piece of writing is not only guided by AI, but can be studied from other aspects, as well as optimizing the relationship between AI and the role of academics.